Tradition and traditional culture as factors of development of global society - Виктор, И. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2017)
In article the traditional culture and tradition as factors of development of the global world, role of traditional values for cultural development is analyzed. Cumulative, dialectic and mythological characteristics of tradition are considered. The concept of parallax allows to explain compatibility of traditional cultures and the global market, mass culture. Dialectic development of tradition includes both disappearance of ethnic stereotypes, and distribution of new myths in local traditions.